A novel function of apolipoprotein E: upregulation of ATP-binding cassette transporter A1 expression. - Yanfeng Zhao; Xinping Chen; Hong Yang; Lichun Zhou; Emmanuel U Okoro; Zhongmao Guo (PLoS ONE)
Despite the well known importance of apolipoprotein (Apo) E in cholesterol efflux, the effect of ApoE on the expression of ATP-binding cassette transporter A1 (ABCA1) has never been investigated. The objective of this study was to determine the effect of ApoE on ApoB-carrying lipoprotein-induced expression of ABCA1, a protein that mediates cholesterol efflux. Our data demonstrate that ApoB-carrying lipoproteins obtained from both wild-type and ApoE knockout mice induced ApoAI-mediated cholesterol efflux in mouse macrophages, which was associated with an enhanced ABCA1 promoter activity, and an increased ABCA1 mRNA and protein expression. In addition, these lipoproteins increased the level of phosphorylated specificity protein 1 (Sp1) and the amount of Sp1 bound to the ABCA1 promoter. However, all these inductions were significantly diminished in cells treated with ApoE-free lipoproteins, when compared to those treated with wild-type lipoproteins. Enrichment with human ApoE3 reversed the reduced inducibility of ApoE-free lipoproteins. Moreover, we observed that inhibition of Sp1 DNA-binding by mithramycin A diminished ABCA1 expression and ApoAI-mediated cholesterol efflux induced by ApoB-carrying lipoproteins, and that mutation of the Sp1-binding motif in the ABCA1 promoter region diminished ApoB-carrying lipoprotein-induced ABCA1 promoter activity. Collectively, these data suggest that ApoE associated with ApoB-carrying lipoproteins has an upregulatory role on ABCA1 expression, and that induction of Sp1 phosphorylation is a mechanism by which ApoE upregulates ABCA1 expression.